Effect of cultivated copepods (Acartia tonsa) in first‐feeding of Atlantic cod (Gadus morhua) and ballan wrasse (Labrus bergylta) larvae. (25th November 2015) - Øie, G.; Galloway, T.; Sørøy, M.; Holmvaag Hansen, M.; Norheim, I.A.; Halseth, C.K.; Almli, M.; Berg, M.; Gagnat, M.R.; Wold, P.‐A.; Attramadal, K.; Hagemann, A.; et al.
Abstract: The aim of this study was to compare the nutritional composition and effects of short periods with cultivated copepod nauplii versus rotifers in first‐feeding. Atlantic cod ( Gadus morhua ) and ballan wrasse ( Labrus bergylta ) larvae were given four different dietary regimes in the earliest start‐feeding period. One group was fed the copepod Acartia tonsa nauplii (Cop), a second fed enriched rotifers (RotMG), a third fed unenriched rotifers (RotChl) and a fourth copepods for the seven first days of feeding and enriched rotifers the rest of the period (Cop7). Cod larvae were fed Artemia sp. between 20 and 40 dph (days posthatching), and ballan wrasse between 36 and 40 dph, with weaning to a formulated diet thereafter. In addition to assessing growth and survival, response to handling stress was measured. This study showed that even short periods of feeding with cultivated copepod nauplii (7 days) had positive long‐term effects on the growth and viability of the fish larvae. At the end of both studies (60 days posthatching), fish larvae fed copepods showed higher survival, better growth and viability than larvae fed rotifers. This underlines the importance of early larval nutrition.